Ablation mechanism of C/C–ZrB2–ZrC–SiC composite fabricated by polymer infiltration and pyrolysis with preform of Cf/ZrB2. (September 2015) - Huang, Dong; Zhang, Mingyu; Huang, Qizhong; Wang, Liping; Xue, Liang; Tang, Xian; He, Kejian
Highlights: The novel C/C–ZrB2 –ZrC–SiC composites were fabricated. A Cf /ZrB2 preform was fabricated by spraying powder during needle-punched process. A ceramic coating was formed around the carbon fibres in the composites. The matrix-modified composites showed a good ablation resistance. Abstract: C/C–ZrB2 –ZrC–SiC composites were fabricated by polymer infiltration and pyrolysis (PIP) with a preform of Cf /ZrB2 . The ZrB2 powders were sprayed onto fabric layer by layer before the fabric is needled. After introduction of resin carbon and ZrC–SiC into the preform, a ceramic coating on the matrix and fibres was formed in the composites. The plasma ablation test indicates that the composites possess a good ablation resistance after ablation for 180 s and 240 s. The SiO2 –ZrO2 barrier layer, high temperature Zr–Si–O glass layer and heat dissipation all contribute to the good ablation resistance of the composites.